(untitled) (Journal of Asian Development Studies, 2024)
This research uses the Socio-Technical Systems (STS) theory postulating that organizational success is a product of social and technical sub-systems, and examine the effects of generative AI on the HR practices. Furthermore, the study focuses on the mediating role of innovation climate on the relationship between generative AI and HR practices in the hospitality sector. A sample of 327 participants is selected by a convenient sampling technique from hotel employees. The data is collected through structured questionnaire and analyzed using PLS-SEM. The results of the study bring essential insights into the interactions between technological dynamics and organizational environments in the case of HR functions in the technology oriented world. Findings shows that generative AI has a massive positive impact on the HR practices and innovation climate positively influence HR Practices. This finding supports the notion that Innovation Climate mediate the relation between generative AI and HR practices. The findings imply that generative AI improves HR Practices but that its full potential is unlocked with a robust innovation climate. The study’s findings contain practical and managerial implications for professionals, managers, and leaders as well as policymakers who desire to improve HR practice and create an innovative environment using generative AI. To attain benefits, HR leaders need to spend as much as they can on the AI driven tools which is capable of doing these processes but handles HR teams to work together to benefit from AI.